Effectiveness of feedback type on performance quality and satisfaction of nursing student: A comparative interventional study - Masoomeh Imanipour; Farshid Mirzaeipour; Mahsa Hazaryan (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Although feedback has a major impact on teaching and learning, the type and way of providing it can have diverse effects. The purpose of this study was to compare the effect of two types of verbal and written feedback on nursing students' performance quality and satisfaction.MATERIALS AND METHODS: This experimental study, that carried out in 2019, has a crossover design. The participants included 30 bachelors of science in nursing at Shushtar Faculty of Medical Sciences, who were assigned to two groups of 15. The first group received first verbal feedback and then written, during basic nursing skills training. The second group received first written feedback and then verbal. At the end of each half of the training sessions, students' performance and their satisfaction were assessed by, researchermade observational checklists, and a satisfaction questionnaire, respectively. Data were analyzed using SPSS16 software and analyzed using Chi-square and paired t test. Significance level < 0.01 was considered.RESULTS: The mean scores of students' performance in the stages of verbal and written feedback were 15.7 ± 2.5 and 17.7 ± 2.3, respectively. Written feedback was more effective in students' performance (P = 0.001) and students were more satisfied with this type of feedback (P = 0.001).CONCLUSIONS: According to the present study, using written feedback can improve the quality of students' performances and is associated with high satisfaction. Thus, professors should pay more attention to feedback in their educational processes and use different types of feedback, especially written feedback, in line with the context.